Benchmarking different fidelities in wind turbine aerodynamics under yaw. Issue 4 (September 2020) - Muñoz-Simón, A; Palacios, R; Wynn, A
Abstract: This paper analyses the aerodynamics of wind turbines under yaw with different modelling fidelities (BEM, BEM with skewed wake model, UVLM and LES-AL). First of all, models are compared in a zero-yaw case to demonstrate their accuracy in prediction of out-of-plane loads and the discrepancy of UVLM in the in-plane loads due to the lack of viscous drag. Secondly, the yaw aerodynamics are described through the advancing/retreating and skewed wake effects, which are appropriately captured by UVLM and LES-AL and lead to an incorrect prediction of the location of maximum and minimum loading along a revolution by BEM. Further, when a skew-wake model is included in BEM, it predicts the correct locations but exhibits overly large loading variations. These predictions are consistent for all yaw angles studied (γ = 10° − 30°). All solvers predict similar decrease of root-bending moments, rotor power and thrust coefficients up to a yaw angle of 10°. However, at larger yaw angles, BEM overpredicts this decrease of coefficients with the yaw angle due to the unsuccessful performance of yaw corrections as opposed to UVLM that inherently accounts for three-dimensional effects. This study demonstrates the need to use computational models that can account for three-dimensional effects in the computation of aerodynamic loads for yaw angles above 10°.